Ecological risk assessment of pesticide residues in arable soils of the Czech Republic - Vašíčková, Jana; Hvězdová, Martina; Kosubová, Petra; Hofman, Jakub (Chemosphere (Oxford), 2019)
Currently used pesticides (CUPs) represent one of the largest intentional inputs of potentially hazardous compounds into agricultural soils. Subsequently, pesticide residues (PRs) and their transformation products (TPs) persist in agricultural soils, occurring in diverse mixtures of compounds in various concentrations. In this study, measured environmental concentrations (MECs) of CUP residues and TPs, originated from previous growing seasons in agricultural soils of the Czech Republic, were used to characterize the environmental risk for agroecosystems. Toxicity exposure ratios (TERs) were calculated using predicted no-effect concentrations (PNECs) and MECs in order to identify single pesticide residues risk to in-soil invertebrates and microorganisms. Ecological risk assessment (ERA) for the mixtures of pesticide residues at each monitored site was assessed using a risk quotient (RQ) method and considering concentration addition among components in the mixtures. The compilation of ecotoxicity data to derived PNECs for in-soil organisms clearly showed data gaps mainly for triazine and chloroacetanilide TPs. In addition, chronic toxicity data for in-soil invertebrates at different trophic levels are not available for 30% of monitored CUPs. The ERA revealed that pesticide residues in soil pose a risk at 35% of the sites (RQ ≥ 1). Among measured pesticides, epoxiconazole, atrazine-2-hydroxy, carbendazim, dimoxystrobin, terbuthylazine and difenoconazole were the main contributors to the overall pesticide mixture toxicity. The measured levels of epoxiconazole together with the frequent presence in soils represent a risk for the agroecosystems. Further assessment of higher tiers of ERA should be considered and prioritized in the pesticides risk management. •The ecological risk assessment of pesticides residues in soil was assessed.•Chronic data are not available for 30% of pesticides and transformation products.•Pesticide residues in soil pose a risk at 35% of the sites.•Triazines and conazole fungicides are main contributors to mixture toxicity at sites.•The levels of epoxiconazole represent a risk and a further assessment should be done.